Sheikh Mujibur Rahman : from rebel to founding father - Badrul Ahsan, Syed, 1954- (Niyogi Books, Pathak Shamabesh (Dhaka), 2014)
On Sheikh Mujibur Rahman, 1922-1975, founder of the nation of Bangladesh.